2013
DOI: 10.1001/jama.2013.3914
|View full text |Cite
|
Sign up to set email alerts
|

Does This Woman Have an Ectopic Pregnancy?

Abstract: ImportanceThe rapid identification and accurate diagnosis of women who may have an ectopic pregnancy is critically important for reducing the maternal morbidity and mortality associated with this condition.Objective To systematically review the accuracy and precision of the patient history, clinical examination, readily available laboratory values, and sonography in the diagnosis of ectopic pregnancy in women with abdominal pain or vaginal bleeding during early pregnancy. Data SourcesWe conducted MEDLINE and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…[50] carried out a systematic review assessing the accuracy and precision of patient history, clinical examination, available laboratory test values, and ultrasonography for the diagnosis of ectopic pregnancy in women with abdominal pain or vaginal bleeding early in pregnancy. They found that all components of patient history had a positive likelihood ratio below 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…[50] carried out a systematic review assessing the accuracy and precision of patient history, clinical examination, available laboratory test values, and ultrasonography for the diagnosis of ectopic pregnancy in women with abdominal pain or vaginal bleeding early in pregnancy. They found that all components of patient history had a positive likelihood ratio below 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] The implementation of point-of-care ultrasound (POCUS), performed by an emergency physician, has already been demonstrated to potentially improve outcome in the pregnant cohort. [8][9][10] Despite this, in many practice environments, specialty-performed ultrasound or radiology department ultrasound (RDUS) is often obtained. As a result of timerelated issues with RDUS, there is an inherent risk of delay in diagnosis and prolongation of ED length of stay (LOS).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 However, if there is also evidence of an adnexal mass then there is a higher likelihood for being an ectopic pregnancy. 5,6 When an ectopic pregnancy is a consideration, a transabdominal ultrasound should be followed by a transvaginal study to adequately evaluate the adnexa. 2,5 When echogenic material, such as clotted blood, is seen within an anechoic uterine sac, the POCUS evaluation can be challenging and must be differentiated from a true yolk sac and fetal pole.…”
Section: Introductionmentioning
confidence: 99%